DIGITISING TO MEET SUSTAINABLE DEVELOPMENT GOALS: CHALLENGES IN THE AFRICAN CONTEXT - Zindi, Beauty; Ndhlovu, Emmanuel (Fakultas Bisnis Universitas Katolik Widya Mandala Surabaya, 2024)
The advent of the Fourth Industrial Revolution (4IR) wields much potential to revolutionize operations and activities and fast-track the attainment of Sustainable Development Goals (SDGs). However, several factors impeding a full-swing technological revolution exist in developing regions like Africa. Drawing on a qualitative semi-systematic literature review underpinned by thematic data analysis, this article explored the challenges of deploying 4IR tools to fast-track the attainment of SDGs. The findings show that limited internet access, underdeveloped ICT infrastructure, regulatory barriers, lack of awareness and education, and lack of collaboration and data sharing are challenges impeding digital adoption to meet SDGs in Africa. To fast-track technology uptake and increase the possibility of achieving SDGs before the 2030 deadline, it is recommended that African governments intervene. This is because most businesses and households in Africa cannot afford digitalization. Most of the households are smallholder farmers. Assisting these farmers with technology would help them increase production and, thus, help eliminate hunger, reduce poverty and gender inequality, promote industry, innovation, and infrastructure, and 12 responsible consumption and production.